The Facilitated Support for Strengthening Statistical Literacy among Fishermen in Burai Village within the Context of Local Fishing Culture - Dian Cahyawati; Eka Susanti; Muji Gunarto; Putri Nilam Cayo; Husnul Khotimah; Andi Tenri Ajeng Nur (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2026)
Background: Burai Village is a riverside fishing community with not high enough levels of formal education and limited use of data in daily decision making. Fishermen typically rely on intuition when planning fishing activities, managing income, and interpreting river conditions. Purpose of the Study: This community service program addressed the need to strengthen statistical literacy as a foundation for data-driven decision making. The program aimed to improve fishermen’s ability to record, organize, and interpret catch data, while increasing awareness of the value of information and simple technology in supporting economic decisions. Methods: A community-based mentoring model was applied, consisting of dialogue sessions, participatory workshops, and hands-on training in data recording. A culturally contextual learning approach linked statistical concepts with local fishing practices. Results: The results demonstrated a measurable improvement in participants’ statistical understanding. The mean score increased from 65 (SD = 21.21) in the pretest to 75 (SD = 10.00) in the posttest, indicating both improved performance and more consistent comprehension among participants. Participants also showed improved ability to interpret tables and graphs and increased interest in using simple digital tools for data documentation.